Implementasi Metode Forward chaining dan Certainty factor dalam Mendiagnosa Autisme Anak Berbasis Web - Kusumanagara, Tasha Fitria; Fauziah, Fauziah; Hidayatullah, Deny (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2021)
Lack of parental or community knowledge of the symptoms of autism in their children results in neglected early detection. This of course can be too late in the treatment of autism in the future. Therefore, this study aims to design a web-based expert system for diagnosing children's autism. The development model used to design an autism expert system in children is a waterfall and implements the forward chaining method and the certainty factor method. While the data collection methods consisted of interview methods and literature study methods. From the results of the calculation test, it is concluded that the results of manual calculations and the web-based application of an expert system for autism diagnosis in children are the same as the results of the 98% confidence level. With this web-based autism expert system in children, it is hoped that it can help parents or the community to detect autism in their children early on.Keywords:Autism, Expert System, Web Based, Forward chaining Method, Certainty factor Method.